2017
DOI: 10.26656/fr.2017.5.051
|View full text |Cite
|
Sign up to set email alerts
|

Retention levels of vegetable extractable beta-carotene preserved in virgin coconut oil and unadulterated honey

Abstract: Dark green leafy vegetables such as Amaranthus spp. are known to be good sources of beta -carotene, a pro-vitamin A carotenoid with highly potent antioxidant property. As an antioxidant, beta-carotene scavenges for electron and thus terminates chain reactions, prevents recurrence and formation of unstable oxygen which otherwise initiate a chain reaction leading to such cases as cancer. While beta-carotene is supplied from consuming vegetables to provide vitamin A, it is also given as a supplement in cases of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We visualized extraction of the carotenoid and its fortification in various matrices as mitigation to its degradation. In a similar study, Mungai et al (2017) reported a 10% retention of beta carotene extracted from Amaranthus spp and preserved in virgin coconut oil and unadulterated honey for 180 days. The study recommended an increase in the amounts of BC in the fortification matrices for higher retentions.…”
Section: Introductionmentioning
confidence: 83%
“…We visualized extraction of the carotenoid and its fortification in various matrices as mitigation to its degradation. In a similar study, Mungai et al (2017) reported a 10% retention of beta carotene extracted from Amaranthus spp and preserved in virgin coconut oil and unadulterated honey for 180 days. The study recommended an increase in the amounts of BC in the fortification matrices for higher retentions.…”
Section: Introductionmentioning
confidence: 83%